A double-layer planning method for integrated community energy systems with varying energy conversion efficiencies. (1st December 2020) - Mu, Yunfei; Chen, Wanqing; Yu, Xiaodan; Jia, Hongjie; Hou, Kai; Wang, Congshan; Meng, Xianjun
Highlights: A dynamic energy hub model considers varying energy conversion efficiencies. The dependency between efficiency and load rate is included in the model. A double-layer planning method is designed based on the model. A case study demonstrates the effectiveness and superiority of this study. Abstract: The energy hub is considered a unit where multiple energy carriers can be converted, conditioned, and stored, thereby providing the functions of input, output, conversion, and storage of multiple energy carriers using a defined coupling matrix. Thus, the energy hub is widely used in the planning and operation of integrated energy systems. However, the coupling factors (or the efficiencies of the energy conversion devices) in the energy hub coupling matrix are usually assumed to be constant for the sake of simplicity, which may result in unreasonable planning and operation schemes for the integrated energy system. For this reason, an integrated energy system planning method at the community level that considers varying coupling factors was developed in this study. First, a dynamic energy hub model was developed, where an efficiency correction model was built to determine the time-varying coupling factors with the variation in load rate. On this basis, a double-layer planning model was built to determine the optimal planning and operation schemes for the integrated community energy system. A typical integrated community energy system was employed as a test system to illustrate the effectiveness of the planning method, and the results were analysed.